Short Communication: Genetic identification of local pigs, and imported pigs Duroc) based on cytochrome b sequence analysis - TETY HARTATIK; BAYU DEWANTORO PUTRA SOEWANDI; SLAMET DIAH VOLKANDARI; ARNOLD CHRISTIAN TABUN; SUMADI SUMADI; WIDODO WIDODO (Society for Indonesian Biodiversity, 2016)
Hartatik T, Soewandi BDP, Volkandari SD, Tabun AC, Sumadi, Widodo. 2016. Genetic identification of local pigs, and imported pigs (Landrace and Duroc) based on cytochrome b sequence analysis. Biodiversitas 17: 270-274. The aim of this study was to identify the genetics of local pigs and imported pigs (from Bali), ix Landrace pigs and four Duroc pigs (from Malang), ine Landrace pigs (from Kupang). Qualitative traits in pigs such as coat color, body shape (back shape, belly shape, and ears) and hair cover were observed. The cytochrome b (Cyt b) gene of mitochondrial DNA was analyzed using PCR-restriction fragment length polymorphism. The PCR analysis resulted in a 464 base pairs (bp) amplified band, and this was digested using TaqI restriction enzyme. The PCR-RFLP analysis resulted in two bands, 246 and 218 bp (monomorphic). The alignment analysis showed four points of single nucleotide polymorphisms. Bali and Kupang pigs had a specific pattern on exterior characteristics such as curved back shape, belly hanging shape, small ears and thick hair, and had many variations on coat color such as black, cream, spotted and mottled. The differences in coat color and body shape, and the corresponding mtDNA Cyt b sequence (with four SNPs) is a marker for genetic variation in pigs.